2015
DOI: 10.4315/0362-028x.jfp-14-382
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Biofilms Formed by Curli- and Cellulose-Expressing Shiga Toxin-Producing Escherichia coli Using Treatments with Organic Acids and Commercial Sanitizers

Abstract: Biofilms are a mixture of bacteria and extracellular products secreted by bacterial cells and are of great concern to the food industry because they offer physical, mechanical, and biological protection to bacterial cells. This study was conducted to quantify biofilms formed by different Shiga toxin-producing Escherichia coli (STEC) strains on polystyrene and stainless steel surfaces and to determine the effectiveness of sanitizing treatments in control of these biofilms. STEC producing various amounts of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
2
4
1
Order By: Relevance
“…Although sanitizer treatments were effective at reducing significantly the viability and the metabolism of STEC in biofilms, the biofilm matrix either remained or was partly removed depending on the sanitizer (Table 2). These results agree with previous reports (6,7,68,69). Moreover, no significant differences in viability or metabolic activity were seen between seropathotypes or isolates (7).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Although sanitizer treatments were effective at reducing significantly the viability and the metabolism of STEC in biofilms, the biofilm matrix either remained or was partly removed depending on the sanitizer (Table 2). These results agree with previous reports (6,7,68,69). Moreover, no significant differences in viability or metabolic activity were seen between seropathotypes or isolates (7).…”
Section: Discussionsupporting
confidence: 82%
“…CF results indicative of curli and/or cellulose production also were variable and are similar to those of other studies (7,8,48). While curli or cellulose production in some STEC isolates was shown to be associated with biofilm formation (6,8,34,(49)(50)(51), these were shown to be nonessential for biofilm formation (7). In our study, no correlation was found between Congo red or calcofluor-positive isolates and biofilm formation or seropathotype (see Fig.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, Meira et al [14] found that biofilms adhered over 4 log CFU/cm 2 on all surfaces at both temperatures and the cell detachment was 3 log CFU/cm 2 . Park and Chen [15] performed a study to quantify biofilms formed by different STEC strains on polystyrene and stainless-steel surfaces to determine the effectiveness of 2% acetic or lactic acid and industry recommended concentrations of acidic or alkaline sanitizers, at 28°C. Results showed that the alkaline and acidic sanitizers were more effective than those with the organic acids for removing the biofilms.…”
Section: Introductionmentioning
confidence: 99%